An enzyme‐linked immunosorbent assay for the measurement of plasma flavonoids in mice fed apigenin‐C‐glycoside. (29th April 2013) - Ninfali, Paolino; Dominici, Sabrina; Angelino, Donato; Gennari, Lorenzo; Buondelmonte, Costantina; Giorgi, Luca
Abstract BACKGROUND In the Chenopodiaceae family, the apigenin flavonoids vitexin‐2‐O‐xyloside (VOX) and vitexin‐2‐O‐rhamnoside (VOR) are important chemopreventive components. To investigate their bioavailability in in vivo animal studies an enzyme‐linked immunosorbent assay (ELISA) method has been developed. RESULTS The ELISA was based on polyclonal antibodies elicited in mice by injecting, as an immunogen, 4′, 6″‐O‐biapigenin (hinokiflavone, HF) conjugated to bovine serum albumin (BSA–HF). A second immunogen was synthesised by coupling an equimolar mixture of VOX and VOR to BSA (BSA–F1). The BSA–HF elicited a significant antibody response, due to 17 HF hapten groups, coupled to each BSA molecule, whereas BSA–F1 provided a very low antigenicity in respect to control animals. Antiserum raised against BSA–HF showed an antibody titre of 1:1600. Antibodies were found to be specific for the flavonols. Our results show that VOX and its metabolic products reached the concentration of 3.42 ± 0.72 µg mL−1 in plasma of VOX fed animals, at the net of the control value. CONCLUSIONS By using the ELISA, the concentration of apigenin flavonoids and their metabolites can be detected in VOX‐ or VOR‐supplemented animals. The assay represents a useful tool for rapid screening to compare bioavailability of apigenin flavonoids in respect to control animals. © 2013 Society of Chemical Industry